Inflection of trembling transition by non-invasive penetration position on ocular humor - Kim, Jeong-Lae; Kang, Eun-Young; Lim, Yun-Sik; Park, Jong-Youel; Hwang, Sung-Ho; Kang, Jeong-Jin (Edelweiss Applied Science and Technology, 2025)
Changes in the use of LEDs in the ocular humor involve a non-invasive technique for examination. The ocular humor was irradiated with a certain amount of LEDs arranged in a circular hemisphere to check the adjacent-angle ocular humor status, which continuously switches to spreading. The change in number was determined by GPPL (Glitter-Proliferation Perceptivity Level), which is formed by the change in spreading perceptivity outward, given the scattering signal generated by the irradiated LEDs over a period of time. The ocular humor is composed of a system that is generated and converted to spreading according to the perceptivity level, and the bumpy conveyance technique was used to confirm the experimental condition of the glitter sphere-vector-dot. The degree of scattering between the microvasculature and the periphery of the foreign body was shown by generating the sphere-vector-dot level in the ocular humor. The maximum GPPL was the result of output formed in the ocular humor status, which yielded the result of the scattering-trembling status. In Spr-POF-FA-αAVG, the spreading far transition due to the spreading sphere-vector-dot trembling was shown as 15.41±8.63 units. In the spreading convenient transition value, Spr-POF-CO-αAVG is 8.70±3.069. In the spreading flank transition value, Spr-POF-SPR-αAVG is 2.65±1.19 units. In the spreading vicinage transition value, Spr-POF-VI-αAVG is 0.51±0.18 units. In GPPL, perceptual level spreading was performed by forming a sphere-vector-dot in the ocular humor status and scattering along the adjacent-angle in the ocular humor outward to evaluate the outward ability of spreading perceptuality. The examination of ocular humor uses a technique (the bumpy conveyance, a non-invasive method) to confirm the glitter-proliferation outward form required for the bumpy conveyance of the perceptual level system. This physiological phenomenon enables the functional properties of the spreading perceptual outward form in the ocular humor and provides a database for utilizing the ocular humor level through a scattering perceptual system.